Miocene–Pleistocene magmas in the Monbetsu area, Northeast Hokkaido, tap N-MORB-like sources contaminated by slab-derived fluids. (May 2015) - Hoang, Nguyen; Miyagi, Isoji; Itoh, Jun'ichi
Highlights: 12–2 Ma intraplate volcanics in northeast Hokkaido, Japan, are reported. Their depletion of HFSE and enrichment of LILE suggest a subduction-related source. The geochemical features are distinct from nearby Eastern Asian intraplate magmas. Sr–Nd–Pb isotopes are N-MORB-like depleted that remain unchanged since 14 Ma. Their source mantle may be blocked following opening tectonics of regional basins. Abstract: Cenozoic intraplate volcanism in northern and northeastern Hokkaido appears to have been closely associated with the Late Oligocene to Mid-Miocene opening of the Japan and Okhotsk Seas (c. 23–12 Ma). Between 12 and 2 Ma, volcanism appeared in the Monbetsu area of northeastern Hokkaido, whose magmatic products are characterized by relative depletions in Nb and Ta and enrichments in LILE and Pb, suggesting a subduction-related source. Likewise, their N-MORB-like isotopic affinity resembles that of active arcs in eastern Hokkaido. These geochemical features are distinct from those of intraplate Cenozoic magmas in Sikhote-Alin, Sakhalin and within the Japan Sea itself, which appear to show a secular change from high- 87 Sr/ 86 Sr, - 206 Pb/ 204 Pb and low- 143 Nd/ 144 Nd (EM2-rich) mantle sources to relatively low- 87 Sr/ 86 Sr and - 206 Pb/ 204 Pb (EM1-rich) types, resembling the progression of magmatic activity during early stages of Japan Sea opening. The EM2 is interpreted to derive from lithospheric mantle while EM1-like components may have been introduced by material delaminated from the Sino-Korea craton, following the Indo-Eurasia collision. In contrast, the Cenozoic Monbetsu volcanics in northern and northeastern Hokkaido appear to lack any such temporal pattern, implying that their respective source regions have not changed since at least c. 14 Ma. We suggest, accordingly, that upper mantle beneath Hokkaido may have been isolated after opening of the Japan and Okhotsk Seas, to the west and northwest, the Kurile Basin to the northeast, and continuing west-vergent subduction of the Pacific plate. Given the fact that Cenozoic volcanism in north and northeastern Hokkaido shows apparent subduction-related character, and that the relationship between this activity and opening of the Kurile Basin remains unclear, we tentatively conclude that intraplate mantle melting may reflect a combination of effects, that of slab-derived hydrous fluid superimposed on upwelling asthenosphere.